1110. Very Late Onset Infections Amongst Long Term Survivors of Kidney Transplantation. (31st December 2020) - Cheung, Harry; Azar, Marwan M; Gan, Geliang; Deng, Yanhong; Cohen, Elizabeth A; Kulkarni, Sanjay; Malinis, Maricar F
Abstract: Background: Kidney transplant recipients (KTR) are at increased risk for infections immediately post-transplant due to intense immunosuppression. However, this risk decreases over time as immunosuppression is tapered. The incidence of infection in KTR many years after transplant is not well characterized. The aim of this study was to describe these "very-late onset infections" (VLIs) ≥ 10 years after KT. Methods: We performed a retrospective chart review of patients age ≥ 18 years who underwent KT between 2003 and 2009 and who survived ≥ 10 years post-KT. VLIs included opportunistic infections (OIs) and non-OIs. Demographics, comorbidities, immunosuppression, and clinical data for VLIs ≥ 10 years from KT were collected. Simple logistic regression was performed to determine characteristics associated with risk for VLIs. Results: Of 332 KTR that met the inclusion criteria, the majority were male (62.0%), white (59.6%), and the largest proportion was transplanted between the ages of 50-59 (28.3%); 220 (67.9%) were on mycophenolate-based regimens. The mean Charlson Comorbidity Index (CCI) was 4.7 (S.D. 2.0). Of 332, 103 (31.0%) KTR experienced ≥ 1 VLI amounting to 187 episodes. Compared to those without VLI, KTR with VLI were more likely to have diabetes (p=0.005), cardiovascular disease (p=0.004), low ALC (p < 0.001) and require dialysis (p=0.002). Of 103 KTR with VLI, 16 (15.5%) had OIs, while 87 KTR (84.5%) had non-OIs, most commonly urinary tract infection (n=85, 45.5%), pneumonia (n=35, 18.7%) and gastrointestinal infection (n=18, 9.6%). The most commonly isolated pathogens were E. coli (n=30, 16%), K. pneumoniae (n=16, 8.6%), MSSA (n=7, 3.7%), and P. aeruginosa (n=7, 3.7%). Higher CCI, diabetes, dialysis, cerebrovascular, cardiovascular disease and lower ALC were associated with increased risk for VLI (p < 0.05), while living donor KTR was protective (p=0.04). Additionally, every 1 year after transplant was associated with an increased risk of VLI (OR=1.31, p < 0.001). Table 1: Demographics, comorbidities, immunosuppression, and clinical data for all patients Conclusion: VLIs were common in long-term survivors of KT and included both conventional and opportunistic pathogens. Every additional year from transplant incurred additional risk for VLI, particularly for those with multiple co-morbidities and lower ALC. Disclosures: All Authors : No reported disclosures